Analisis Pengaruh Pengetahuan Peraturan Perpajakan, Pelayanan Perpajakan, Dan Sosialisasi Perpajakan, Terhadap Kepatuhan Wajib Pajak (Studi Empiris Pada Kantor Pelayanan Pajak Medan Kota) - Amran Manurung; Bonifasius H Tambunan; Andalkris Laia (Jurnal Riset Akuntansi dan Bisnis, 2023)
The purpose of this study was to analyze the effect of knowledge of tax regulations, tax services, and tax socialization on taxpayer compliance with sanctions as a moderating variable at the Medan City Tax Service Office. The type of research used is causality. The population in this study are individual taxpayers who are registered at the Medan City Tax Service Office. The sampling method used in this study is non-probability sampling, namely incidental sampling. The type of data used in this research is primary data. The analytical method used is multiple linear regression analysis and interaction test. The results of this study indicate that knowledge of tax regulations, tax services, and tax socialization simultaneously have a significant effect on taxpayer compliance. Knowledge of tax regulations has a positive and significant effect on taxpayer compliance. Tax services have a positive and significant effect on taxpayer compliance. Tax socialization has a negative effect on taxpayer compliance.